Medicinal plants used in Hmong women's healthcare in northern Thailand - Srithi K. (2014)
Ethnopharmacological relevance: We studied traditional knowledge of medicinal plants used for women's healthcare in three Hmong villages in northern Thailand and determined how prevalent such knowledge is. We documented traditional medical practices and determined which of the species used are culturally important among the Hmong. Materials and methods: We interviewed six key informants and 147 non-specialist informants about their traditional knowledge of medicinal plants used in Hmong women's healthcare. We selected nine species that were known in all three villages as the domain for questionnaire interviews with 181 additional and randomly selected non-specialist informants. We calculated the Cultural Importance index (CI) for each species and use category. We tested normality of the data, age correlations, and gender correlations with Kolmogorov-Smirnov tests, Spearman's rank correlation coefficient, Kruskal-Wallis test, and Mann-Whitney tests. Results: We documented traditional knowledge of 79 medicinal plants used in women's healthcare. Of these, three species were culturally important to the Hmong. Our questionnaire interviews revealed significant difference in traditional medicinal plant knowledge between genders and age groups. Conclusions: The Hmong people in northern Thailand possess large amounts of traditional knowledge related to women's healthcare and plants used for this purpose. However, this knowledge, even for the culturally important species, is not possessed by all Hmong and there were signs of knowledge erosion. Preservation of the Hmong intellectual heritage related to medicinal plants used in women's healthcare requires intensive traditional knowledge dissemination to the young Hmong generation. © 2011 Elsevier Ireland Ltd. All rights reserved.